Innovation of vertical intra-industry trade: Asean-5 and China electronic and telematic sectors - Deni Kusumawardani, Galih Dwika Putra Ragayatsu, (Opción, 2020)
Globalization can create opportunities and challenges, so that optimizing and minimizing the impact of globalization requires innovation. The way to increase innovation is through development in priority industries that are able to provide spillover effects on technology and international trade. The purpose of this study is to analyze the direct influence of vertical intra-industry trade in the electronics and telematics industries on innovation in ASEAN-5 and China. The results showed that the greater technological gap between developed countries and ASEAN-5 and China, the greater the effect of technological diffusion from intra-industrial trade.